Who talks to whom in african agricultural research information networks?: The Malawi case - Droppelmann, Klaus; Mapila, Mariam A.T.J.; Mazunda, John; Thangata, Paul Howard; Yauney, Jason (International Food Policy Research Institute, 2013)
Although it is recognized that agricultural research plays a vital role in ensuring success of sectorwide agricultural development strategies, there has been little or no effort to explicitly link the research strategies of the National Agricultural Research System (NARS) in African countries to the research agenda that is articulated in sectorwide agricultural development strategies. This study fills that gap by analyzing the readiness of Malawi’s NARS to respond to the research needs of the national agricultural sector development strategy, namely the Agriculture Sector Wide Approach (ASWAp) program.